2015
DOI: 10.1002/ptr.5524
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Curcumin Administration in Patients with Major Depressive Disorder: Mini Meta-Analysis of Clinical Trials

Abstract: Major depression is a common, recurrent, and chronic disease that negatively affects the quality of life and increases the risk of mortality. Several studies have demonstrated that curcumin, the yellow-pigmented substance of the turmeric, possesses antidepressant properties. The aim of this review is to meta-analytically assess the antidepressant effect of curcumin in patients with major depressive disorders. We extensively searched the literature until August 2015. The random-effect model was used to calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 60 publications
1
52
0
4
Order By: Relevance
“…Meta-analysis of clinical trials demonstrated that adjunctive treatment with curcumin might be beneficial in terms of improvement in depressive symptoms in patients with MDD, especially in middle-age patients with longer duration of administration and at higher doses (Al-Karawi et al, 2016). More recently, effects of curcumin at different doses (250 mg b.i.d.…”
Section: Curcuminmentioning
confidence: 98%
“…Meta-analysis of clinical trials demonstrated that adjunctive treatment with curcumin might be beneficial in terms of improvement in depressive symptoms in patients with MDD, especially in middle-age patients with longer duration of administration and at higher doses (Al-Karawi et al, 2016). More recently, effects of curcumin at different doses (250 mg b.i.d.…”
Section: Curcuminmentioning
confidence: 98%
“…Preclinical and clinical evidences demonstrated that curcumin has a strong potential to protect against oxidative stress, inflammation, cancer, and metabolic and neurological diseases (Kunnumakkara et al, , Al‐Karawi, Al Mamoori, & Tayyar, , Daily, Yang, & Park, , Sahebkar & Henrotin, , Nasseri et al, ). In the present study, it was observed that curcumin supplementation significantly reduced serum NTBI, an index of free iron, in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sign Path Pharm PA USA has prioritized cancer treatment for Lipocurc in the research and development (R/D) platform; however, we consider it worthwhile to repurpose Lipocurc for likely therapeutic effects in schizophrenia. A recent RCT study found infusion of nitroprusside in modulating NMDA receptor, significantly improved the positive, negative, depressive and anxiety symptoms: the changes in Brief Psychiatric Rating scale: BPRS scores persisted for 4 weeks post-infusion [72]. No adverse events were reported.…”
Section: Lipocurc Tm Infusion: Lead Drug On the Horizon For Schizophrmentioning
confidence: 93%